Reaping the rewards of foreign direct investment: Linkages between extractive MNCs and local firms in Tanzania - Michael W. Hansen (Danish Institute for International Studies (DIIS), 2013)
After a decade of steadily growing foreign direct investment (FDI) in extractives, Tanzania is now facing a virtual 'take off'' in extractive FDI. One of the concerns related to these investments is whether the foreign investors are linking up sufficiently with local firms through localized supply chains and service inputs. In theory, the opportunities for linkage formation in Tanzania are due to the growing propensity of extractive multinational corporations (MNCs) to outsource sections of their value chain. However, our review demonstrates that linkages in Tanzanian extractives are few and that those that do exists are typically shallow and confined to simple, low value added tasks. The reason for the lack of linkages is mainly that the technology gap between MNCs and local firms is too big to bridge and that a toxic Tanzanian business environment makes contractual partnerships between local firms and MNCs difficult. The lack of linkages amplifies already widespread concerns that extractive FDI leaves too few development benefits for Tanzanian society. As a consequence, pressure is mounting on the government to force MNCs into localizing their value chains though mandatory local content and ownership requirements. The paper assesses the diverging interests and pressures for linkage formation in Tanzanian extractives and discusses whether or not the Tanzanian government will be able to exploit the opportunity offered by the surge in extractive FDI to spur economic development and industrial transformation. The conclusion is that there is a risk that Tanzania will forego this development opportunity due to lack of focused industrial vision and policy.
Keywords: 300